An analysis of the policy responses to the COVID-19 pandemic in France, Belgium, and Canada. Issue 4 (December 2020) - Desson, Zachary; Weller, Emmi; McMeekin, Peter; Ammi, Mehdi
Highlights: France, Belgium and Canada have varied degrees of governance. Higher data integration and resource coordination is achieved in centralized France. But decentralized Canada built testing capacity quickly, with variation across provinces. Shared decision making between national and subnational in Belgium may be least effective. Abstract: Objectives: This paper presents an overview and comparative analysis of the epidemiological situation and the policy responses in France, Belgium, and Canada during the early stages of the 2020 Covid-19 pandemic (Feb.-Aug. 2020). These three countries are compared because they represent a spectrum of different governance structures while also being OECD nations that are similar in many other respects. Methods: A rapid review of primary data from the three countries was conducted. Data was collected from official government documents whenever possible, supplemented by information from international databases and local media reports. The data was then analysed to identify common patterns as well as significant divergences across the three countries, especially in the areas of health policy and technology use. Results: France, Belgium and Canada faced differing epidemiological situations during the Covid-19 pandemic, and the wide variety of policy actions taken appears to be linked to existing governance and healthcare structures. The varying degrees of federalism and regional autonomy across the three countries highlight the different constraints faced by national policy-makers within different governance models. Conclusions: The actions taken by all three countries appear to have been largely dictated by existing health system capacity, with increasing federalism associated with more fragmented strategies and less coordination across jurisdictions. However, the implications of certain policies related to economic resilience and health system capacity cannot yet be fully evaluated and may even prove to have net negative impacts into the future.